A new inverse kinematics algorithm for binary manipulators with many actuators - Jackrit Suthakorn (2011)
In this paper we present a new, and extremely fast, algorithm for the inverse kinematics of discretely actuated manipulator arms with many degrees of freedom. Our only assumption is that the arm is macroscopicallyserial in structure, meaning that the overall structure is a serial cascade of units with each unit having either a serial or parallel kinematic structure. Our algorithm builds on previous works in which the authors and coworkers have used the workspace density function in a breadth- rst search for solving the inverse kinematics problem. The novelty of the method presented here is that only the ‘mean’ of this workspace density function is used. Hence the requirement of storing a sampled version of the workspace density function (which is a function on a six-dimensional space in the case of a spatial manipulator) is circumvented. We illustrate the technique with both planar revolute and variable-geometry-trussmanipulators, and brie y describe a new manipulator design for which this algorithm is applicable.